Quantification and classification of solid-ordinary waste of Universidad Nacional de Costa Rica into the landfills - Rojas-Vargas, Julián; Bogantes, Joseline (Uniciencia, 2018)
The study of the composition of ordinary waste sent to landfills aims to determine the generation rates and types of waste generated in the Universidad Nacional de Costa Rica (National University of Costa Rica-UNA) and disposed in landfills, in order to sensitize the university population to contribute to the responsible and integral management of solid waste, reducing the disposal of these in sanitary warehouses. For this purpose, a sampling methodology was used, taking the entire set up for two full days, with a total of 23 sampling points. This study was carried out with a team of third‑year students from the environmental management career. It was found that the main waste generated is organic, with a potential use of 100% by 2015 (Garita and Rojas, 2015a); an average of 60% of the waste can be recovered or used as a raw material in a comprehensive management plan, a fact that is much less than the national percentage of 93.6% (Paniagua, Giraldo y Castro, 2011).